Death and Salvation in "The Heights of Fear" by the Novelist Hazzaa Al-Barari - Abdel-Rahman Obaid, Linda (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to examine the novel "Heights of Fear" with a focus on the manifestations of death within it, as well as the diverse attempts at salvation and liberation, varying according to the perspectives and struggles of the characters. Methods: The study adopts a textual analytical approach, drawing insights from psychological and social studies to explore the theme of death in the novel "Heights of Fear." It views the narrative structure as an integrated entity, combining form and content. Results: The novel, preoccupied with questions of existence and human destiny, expresses its vision through a coherent narrative structure and literary techniques. Death looms over the fates of the characters, the features of the universe, and the details of nature, keeping questions unanswered and responses varied, reflecting the alienation of the contemporary intellectual and the triumph of consciousness and life despite the tragic nature of destiny. The novel presents three approaches in attempting to escape and find salvation from death: the violation of the body, the psychological withdrawal and self-enclosure, and the employment of prophecy and myth. However, these attempts remain futile and unattainable, failing to achieve true salvation. Conclusion: The pursuit of salvation in the novel "Heights of Fear" takes various paths, but ultimately proves to be a closed and futile endeavor. Anxiety prevails, and suffering intensifies, leading the characters to endure their tragic destinies in a reality riddled with defeats, setbacks, and fractures. Death remains a concealed mystery and an existential question disturbing human serenity, within the eternal struggle between life and mortality.